2024
DOI: 10.1021/acs.cgd.4c00233
|View full text |Cite
|
Sign up to set email alerts
|

On Solute Recovery and Productivity in Chiral Resolution through Solid-State Deracemization by Temperature Cycling

Mercedeh Sadat Hosseinalipour,
Leif-Thore Deck,
Marco Mazzotti

Abstract: Temperature cycling represents an effective means for the deracemization of chiral compounds that crystallize as conglomerates and racemize in solution. In such a process, a suspension enriched in the desired enantiomer is converted into an enantiopure one through periodic cycles of crystal dissolution and crystal growth. We show that performing temperature cycling at higher temperatures leads to faster deracemization and, consequently, higher productivity. However, this comes at the cost of lower recovery, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, neither work presented promising yields to demonstrate the potential of this method. The compound specific effects are also clear, as 1 crystallizes differently to the other molecules studied, and do not undergo thermal decomposition, as seen for glutamic acid in the work by Pálovics et al, and the cooling rates that induced nucleation in the work of Hosseinalipour et al, was not observed for 1 [15,16].…”
Section: Tcid Coupled With Soat-based Coolingmentioning
confidence: 81%
See 1 more Smart Citation
“…However, neither work presented promising yields to demonstrate the potential of this method. The compound specific effects are also clear, as 1 crystallizes differently to the other molecules studied, and do not undergo thermal decomposition, as seen for glutamic acid in the work by Pálovics et al, and the cooling rates that induced nucleation in the work of Hosseinalipour et al, was not observed for 1 [15,16].…”
Section: Tcid Coupled With Soat-based Coolingmentioning
confidence: 81%
“…by favoring the crystal growth of the major enantiomer. This simple cooling technique has been demonstrated by Palovics et al and Hosseinalipour et al however, neither team demonstrated favorable experimental mass yields [15,16].…”
Section: Introductionmentioning
confidence: 94%